Clinical validity of a population database definition of remission in patients with major depression - Salvatella-Pasant Jordi; Gutiérrez-Nicuesa Laura; Blanca-Tamayo Milagrosa; Sicras-Mainar Antoni; Navarro-Artieda Ruth (BMC, 2010)
Abstract Background Major depression (MD) is one of the most frequent diagnoses in Primary Care. It is a disabling illness that increases the use of health resources. Aim: To describe the concordance between remission according to clinical assessment and remission obtained from the computerized prescription databases of patients with MD in a Spanish population. Methods Design: multicenter cross-sectional. The population under study was comprised of people from six primary care facilities, who had a MD episode between January 2003 and March 2007. A specialist in psychiatry assessed a random sample of patient histories and determined whether a certain patient was in remission according to clinical criteria (ICPC-2). Regarding the databases, patients were considered in remission when they did not need further prescriptions of AD for at least 6 months after completing treatment for a new episode. Validity indicators (sensitivity [S], specificity [Sp]) and clinical utility (positive and negative probability ratio [PPR] and [NPR]) were calculated. The concordance index was established using Cohen's kappa coefficient. Significance level was p < 0.05. Results 133 patient histories were reviewed. The kappa coefficient was 82.8% (confidence intervals [CI] were 95%: 73.1 - 92.6), PPR 9.8% and NPR 0.1%. Allocation discrepancies between both criteria were found in 11 patients. S was 92.5% (CI was 95%: 88.0 - 96.9%) and Sp was 90.6% (CI was 95%: 85.6 - 95.6%), p < 0.001. Reliability analysis: Cronbach's alpha: 90.6% (CI was 95%: 85.6 - 95.6%). Conclusions Results show an acceptable level of concordance between remission obtained from the computerized databases and clinical criteria. The major discrepancies were found in diagnostic accuracy.